Strategic roadmap on mainstreaming gender-smart investing to scale climate smart agriculture in sub-Saharan Africa - Derenoncourt, Marie Ena; Cosgrove, Bethany Emma; Grosjean, Godefroy; Newman, Richard (2022)
This note proposes a roadmap to advise public and private investors, banks, corporates, and NGOs, on how to mainstream gender smart investing to scale climate-smart agriculture (CSA). Based on private sector consultation and secondary research, the note provides check lists to guide the reader step-by-step and makes recommendations on how different actors can engage by building internal capacity in CSA and gender-smart approaches, integrating gender dimensions when assessing CSA business models, using gender-smart techniques in the investment process, making the most of existing gender responsive innovative financial instruments.